Pengaruh Pengeringan terhadap Karakteristik Teh Herbal Celup Rimpang Temu Putih (Curcuma zedoaria Rosc.) - Komariah, Risti; Trisna Darmayanti, Luh Putu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
Abstract The purpose of this research was to find out the effect of drying on the characteristics of zedoary rhizome herbal tea bag (Curcuma zedoaria Rosc.) and to determine of drying that able to produce zedoary rhizome herbal tea bag with the best characteristics. The Completely Randomized Design (CRD) was used in this research with four drying treatments such as, drying using an oven at 50 oC for 24 hours, drying using sunlight at ± 40 oC for three days, drying using room temperature or dry wind at ± 26 oC for six days, and drying by roasting at ±50 oC for 45 minutes. All of the drying were repeated four times to obtain 16 units of experiment. The analysis of variance (ANOVA) used to get data and if the drying had a significant effect, it was followed by the Duncan Multiple Range Test. The results showed that drying had a significant effect (P <0,01) on total curcuminoids, total phenols, total flavonoids, and sensory analysis of colour (scoring test). Drying using room temperature or dry wind had the best characteristic of zedoary rhizome herbal tea bag with content: total curcuminoid of  29,10 mg CE / g, total phenol of 167,51 mg GAE / g, and total flavonoid of 41,47 mg QE / g. The characteristics of the brewed water of zedoary rhizome herbal tea bag were dark yellow color and liked, the flavour distinctive of herbal tea zedoary rhizome and liked, the taste was bitter and usual, and overall acceptance was usual.